Design Build Canteen Web Applications in Majalengka University: Contemporary Ways to Boost User Satisfaction and Management in the Campus Environtment - Dhiyauddin, Muhammad Dziya; Cesoria, Yola Zerlinda; Al-Saud, Abdal Aziz (West Science Interdisciplinary Studies, 2024)
For Majalengka university, a web-based canteen application has been developed as a modern solution in response to the growing demand for effective and user-friendly campus services. The goal of this project is to create and deploy a cutting-edge application that improves user satisfaction and expedites campus environment management procedures. The application combines state-of-the-art technologies to offer users—including staff, instructors, and students—a seamless and accessible experience. Real-time inventory management, safe payment methods, and online ordering are important features. The responsive design accommodates the varied tastes and needs of the campus community while guaranteeing accessibility across a range of devices. The canteen hopes to streamline operations by using this web application, which will improve order processing efficiency and cut down on wait times. The system also helps with improved resource and inventory management, guaranteeing customers a reliable and excellent dining experience. In addition to meeting the needs of the campus community today, this project establishes a standard for the use of technology to improve administration and services in educational settings. The findings of this research offer significant contributions to the development and execution of web-based canteen management applications, and may have consequences for comparable settings outside of Majalengka university.